Luteolin alleviates CUMS-induced depressive-like behavioral deficits in mice through blocking the JAK2/STAT3 pathway - Hai-hong Wu; Shang-yue Chen; Dong-liang Yuan; Ting Zhao (PLoS ONE, 2025)
This study probed into the potential effects of luteolin (LUT) on depressive-like behavioral deficits caused by chronic unpredictable mild stress (CUMS) in mice, with a focus on its underlying molecular mechanisms. Western blot analysis revealed that CUMS notably activated the JAK2/STAT3 pathway, as indicated by elevated levels of phosphorylated JAK2 (p-JAK2) and p-STAT3. Treatment with LUT notably diminished p-JAK2 and p-STAT3, suggesting that LUT alleviates CUMS-induced depressive-like behavioral deficits by blocking the JAK2/STAT3 pathway. Behavioral assessments, including the forced swim and sucrose preference tests, demonstrated that LUT remarkably improved depressive-like symptoms. Furthermore, LUT treatment diminished the levels of pro-inflammatory cytokines, which were elevated by CUMS, further supporting the involvement of LUT in exerting antidepressant activities via the modulation of inflammatory responses. This study is the first to integrate multidimensional evidence from behavioral tests, neuroinflammation, and the JAK2/STAT3 signaling pathway, systematically demonstrating that luteolin alleviates CUMS-induced depression-anxiety comorbidity through synergistic regulation of an antioxidant‒anti-inflammatory‒neural signaling network.